Flexibility vs. Rigidity: Does Spain have the worst of both Worlds? - Gilles Saint-Paul (Institute for the Study of Labor (IZA), 2000)
In this paper we study the structure of labor market flows in Spain and compare them with France and the US. We characterize a number of empirical regularities and stylized facts. One striking result is that the job finding rate is slightly higher than in France, while the job loss rate is much higher, putting Spain half-way between France and the US. This suggests that while Spain has borne the full cost of its labor market reforms in terms of job precarity, the benefits in terms of job creation have been quite modest. We hypothesize that this has been due to the reform's credibility being imperfect, which leads to expectation of reversal.
Keywords: J20; J21; J23; J63; J41; J42; E24; 330; Unemployment; flexibility; temporary contracts; unemployment duration; unemployment recurrence; on the job search; labor force composition; Arbeitsmobilität; Arbeitslosigkeit; Arbeitsmarktpolitik; Spanien; Frankreich; USA